Evaluation of Yeast Culture Supplementation on Milk Yield and Rumen Fermentation in Dairy Cows - A Field Study in Chhattisgarh - Shukla, Namita; Tiwari, Ashutosh; Sharma, Kranti; Yadav, Renu (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Low milk yield remains a significant challenge for smallholder dairy farmers in Chhattisgarh, India, due to suboptimal nutrition and inefficient rumen fermentation. This study evaluated the effects of dietary supplementation with Saccharomyces cerevisiae yeast culture on milk production and rumen fermentation characteristics in lactating crossbred cows (30-60 DIM) under field conditions in Dhamtari and Raipur districts. A total of 40 cows were randomly allocated into two groups: Control (basal diet only) and Treatment (basal diet plus 10 g/day of yeast culture) over a 90-day period. Results showed a statistically significant improvement (p<0.01) in average daily milk yield in the yeast-supplemented group compared to the control (13.2±0.8 Vs. 11.1 ± 0.7 L/day), though the milk composition did not vary significantly. Additionally, rumen pH was better stabilized, total volatile fatty acids (TVFA) production was higher, and ammonia-N concentration was reduced in the treatment group, indicating improved rumen fermentation efficiency. These findings suggest that yeast culture supplementation is an effective and low-cost strategy for improving dairy productivity and rumen health in smallholder systems prevalent in tropical regions.